Alternatif Pendanaan Melalui Sekuritisasi Aset (KIK- EBA) Studi Kasus PT Adhi Commuter Properti - Siti Maesaroh; Nanu Hasanuh (Jurnal Ilmiah Wahana Pendidikan, 2022)
Asset equity is the receipt of future income that will be received at this time so that it can overcome funding problems. This study aims to provide reference material for corporate policy makers related to securitization through the issuance of Asset Backed Securities to obtain optimal funding alternatives. The research method used is descriptive research. The method of data collection was carried out by field research and library research. Asset securitization mechanisms include: pre-transaction preparation phase, current transaction phase, and post-transaction phase. The costs incurred include: upfront fees, transaction fees, and other costs. Risks in asset securitization include: credit risk, geographic concentration risk on financed property, liquidity risk, early repayment risk, and legal risk. The conclusion of this study is that companies can obtain funding that is cheaper and faster than having to wait until the bill is due by using the KIK-EBA scheme